Pengaruh Biaya Produksi dan Harga Jual Terhadap Pendapatan Petani Jagung Pada Petani Jagung Nagari Aie Tajun Kecamatan Lubuk Alung: Petani Jagung Nagari Aie Tajun Kecamatan Lubuk Alung - Syukrial; Halimah, Halimah; Hendri, Novi (Universitas Sumatera Barat, 2024)
This research was conducted to determine the effect of production costs and selling prices on the income of Nagari Aie Tajun corn farmers, Lubuk Alung District. This type of research is quantitative and primary source research. The population in this study were corn farmers in Nagari Aie Tajun, Lubuk Alung District. The sample size can be determined using the Slovin formula, so a sample of 82 respondents is obtained. Data collection techniques using questionnaires. Test the research instrument using validity and reliability tests. The classical assumption test used is normality, multicollinearity and heteroscedasticity tests. To test the hypothesis, the T test, F test and Adjusted R Square test are used. The analytical tool used is multiple linear regression with the help of SPSS version 22. The results of the research show that the variables of production costs and selling prices have a significant effect on the income of Nagari Aie Tajun farmers, Lubuk Alung District. This is proven by the value of tcount > ttable with a significance level of less than 0.05. The variables of production costs and selling prices simultaneously influence the income of Nagari Aie Tajun corn farmers, Lubuk Alung District. This is proven by the value of fcount > ftable. The contribution of the variables together is 51.9% of the dependent variable, 48.1% is influenced by other variables not examined in this research.